Pengaruh PENGARUH PERENCANAAN STRATEGIS DAN EFIKASI DIRI TERHADAP KEMAMPUAN MENULIS ARGUMENTASI: - - Cholifah, Maria; herawati, siane (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2022)
This study aims to (1) measure the effects of the students taught by using strategic planning and non-strategic planning in the argumentative essay writing; (2) measure the effects of the students having high and low self-efficacy in the argumentative essay writing, and (3) measure the interaction effects between strategic planning and self-efficacy on the students’ argumentative essay writing skill. The research design used in this study was experimental research with two way ANOVA. This research was conducted in for students in the English Language Education and English Literature Study Program, PGRI Kanjuruhan University of Malang who took the Essay Writing course. The results of this study indicate that students taught by using strategic planning got higher scores than students taught by using non-strategic planning. This can be seen from the mean value in the experimental class (strategic planning) is 84.57, while the average of students in the control class (non-strategic planning) is 64.37. Meanwhile the students who have high self-efficacy got higher scores than students having low self-efficacy. This can be seen from the average score of students with high self-efficacy is 79.67, while the average value of students with low self-efficacy is 59.87. There is also an interaction between strategic planning and self-efficacy on the students’ ability in writing argumentative essay. The significance is .000 which is smaller than .05.